Analysis of Attendance System for Discipline Enforcement of Bappeda Fakfak Employees - Jamaluddin, Jamaluddin; La Alimuda, Risnayati; Isgunandar, Isgunandar (ASHA Publishing, 2024)
The employee attendance system is a data collection on employee attendance which is part of the reporting activity in an agency in helping to improve order and discipline in the work environment. In Bappeda Fakfak, it was found that the attendance system in this office uses manual attendance. Previously, the Bappeda Fakfak office implemented a fingerprint attendance system or fingerprint machine but it did not last long, because the fingerprint machine or fingerprint machine was damaged so it returned to using the manual attendance system. found several employees who were less disciplined, this was proven by the fact that there were still employees who did not arrive on time according to office hours, besides that there were employees who only left their attendance because there were sudden activities so they could not directly fill in the attendance. This study aims to enforce discipline of Bappeda Fakfak employees. This study is qualitative, therefore, to achieve the objectives of the study, data collection techniques were used, namely observation, interviews, in this study there were 5 informants, namely the secretary of Bappeda Fakfak, the Head of the general and personnel sub-section, and 3 Bappeda Fakfak employees. Based on the results of this study, it shows that the discipline of Bappeda Fakfak employees is in the category of